2009
DOI: 10.2967/jnumed.108.058347
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT with 99mTc-MAA in Radioembolization with 90Y Microspheres in Patients with Hepatocellular Cancer

Abstract: Radioembolization with 90 Y microspheres is a novel treatment for hepatic tumors. Generally, hepatic arteriography and 99m Tc-macroaggregated albumin (MAA) scanning are performed before selective internal radiation therapy to detect extrahepatic shunting to the lung or the gastrointestinal tract. Whereas previous studies have used only planar or SPECT scans, the present study used 99m Tc-MAA SPECT/CT scintigraphy (SPECT with integrated low-dose CT) to evaluate whether SPECT/CT and additional diagnostic contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 19 publications
(32 reference statements)
3
55
0
2
Order By: Relevance
“…There is broad agreement on SPECT-CT being more clinically useful in terms of extrahepatic uptake and more accurate in terms of activity quantification than either SPECT or planar imaging [18][19][20] with a recent study of 58 patient scans showing rates of detection of extrahepatic MAA was 72%, 79% and 96% for planar, SPECT and SPECT-CT, respectively [21]. Other studies have identified extrahepatic uptake on SPECT-CT not discernable on planar or SPECT only, leading to treatment adjustments such as additional surgical embolization [18,22].…”
Section: Methodsmentioning
confidence: 99%
“…There is broad agreement on SPECT-CT being more clinically useful in terms of extrahepatic uptake and more accurate in terms of activity quantification than either SPECT or planar imaging [18][19][20] with a recent study of 58 patient scans showing rates of detection of extrahepatic MAA was 72%, 79% and 96% for planar, SPECT and SPECT-CT, respectively [21]. Other studies have identified extrahepatic uptake on SPECT-CT not discernable on planar or SPECT only, leading to treatment adjustments such as additional surgical embolization [18,22].…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivities were 100, 41 and 32 % and the specificities 98, 98 and 93 % for SPECT/CT, SPECT and planar imaging, respectively. In a prospective study Hamami et al [27], evaluating 68 99m Tc-MAA procedures performed in 58 patients with HCC, demonstrated a superior performance of SPECT/CT over SPECT and planar imaging (sensitivity 100 %, specificity 94 % for SPECT/CT versus 56 and 87 %, respectively, for SPECT). Similarly, in a report published by Lenoir et al [28] the superiority of SPECT/CT over planar imaging was demonstrated analyzing 136 hepatic perfusion scintigraphies.…”
Section: Hepatic Perfusion Imagingmentioning
confidence: 99%
“…Transaxial and sagittal reconstructed SPECT/CT image shows 99m Tc-MAA uptake within anterior abdominal wall due to flow from falciform artery, which originated from middle hepatic artery. (10,(12)(13)(14)(15)(16). This study reports our experience in treatment planning for 174 patients.…”
Section: Figurementioning
confidence: 99%
“…1-3). A detailed discussion of considerations of normal hepatic perfusion and hepaticoenteric arterial anatomy in the context of radioembolization has been published elsewhere (10,(12)(13)(14)(15)(16). In a recent publication by Ilhan et al, SPECT/CT images were reviewed for tumor uptake distribution and graded on the basis of the concentration of 99m Tc-MAA and distribution within the tumor (17).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation